Covering and explaining conflict in civil society - Nalini Rajan (ed.) (Hyderabad: Orient BlackSwan, 2014)
Contributed articles.
Keywords: Civil Society; Conflict Management; Social Conflict Mass Media; Social Media; Social Sciences